2023
DOI: 10.1039/d3ee00084b
|View full text |Cite
|
Sign up to set email alerts
|

Distinct thermal runaway mechanisms of sulfide-based all-solid-state batteries

Abstract: All-solid-state batteries (ASSBs) are one of the most promising candidates for next-generation energy storage. In particular, ASSBs with sulfide solid-state electrolytes (SEs) offer high conductivity, rivaling those of liquid electrolytes...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(25 citation statements)
references
References 69 publications
0
25
0
Order By: Relevance
“…Rui et al investigated the TR behaviors of sulfide SSEs when paired with NMC811 cathodes. [151] It is revealed that there are two distinct TR mechanisms of sulfide SSEs, the gas-solid and the solid-solid reactions, which correspond to glassy-ceramic (Li 3 PS 4 and Li 7 P 3 S 11 ) and crystalline (Li 6 PS 5 Cl and Li 10 GeP 12 S 2 ) SSEs, respectively. As shown in Figure 9e, the glassy-ceramic SSEs were oxidized by O 2 released from the NCM811 cathode at approximately 200 °C, resulting in tremendous heat and generation of toxic SO 2 gas.…”
Section: Inorganic Ssesmentioning
confidence: 99%
See 1 more Smart Citation
“…Rui et al investigated the TR behaviors of sulfide SSEs when paired with NMC811 cathodes. [151] It is revealed that there are two distinct TR mechanisms of sulfide SSEs, the gas-solid and the solid-solid reactions, which correspond to glassy-ceramic (Li 3 PS 4 and Li 7 P 3 S 11 ) and crystalline (Li 6 PS 5 Cl and Li 10 GeP 12 S 2 ) SSEs, respectively. As shown in Figure 9e, the glassy-ceramic SSEs were oxidized by O 2 released from the NCM811 cathode at approximately 200 °C, resulting in tremendous heat and generation of toxic SO 2 gas.…”
Section: Inorganic Ssesmentioning
confidence: 99%
“…(e) Schematic diagram of the two distinct failure routes of different sulfide SEs with NCM811. Reproduced with permission [151]. Copyright 2023, Royal Society of Chemistry.…”
mentioning
confidence: 99%
“…In addition, other works have highlighted the existence of different failure modes even within NCM sulfide-based SSBs. Glass-ceramic solid electrolytes (Li 3 PS 4 and Li 7 P 3 S 11 ) together with LiNi 0.8 Co 0.1 Mn 0.1 O 2 were observed to undergo thermal runaway mechanisms originating from gas–solid reactions which also resulted in SO 2 generation, while in crystalline solid electrolytes (Li 6 PS 5 Cl and Li 10 GeP 12 S 2 ), thermal runaway reactions in LiNi 0.8 Co 0.1 Mn 0.1 O 2 SSB were found to be driven by solid–solid reactions between the solid decomposition products of NCM and the solid electrolyte . Therefore, beyond the thermal stability of the electrolyte alone, more studies are needed to assess the relative chemical and electrochemical stability of the active material and solid electrolyte combination at various states of charge.…”
Section: Opportunities and Directions For Further Researchmentioning
confidence: 99%
“…While the limited reversibility and cycle life of conversion reactions have historically inhibited the entrance of transition metal sulfides into the commercial rechargeable battery space, the re-emergence of SSB research offers new opportunities to revisit sulfide conversion chemistries. Some of these reasons include the increased external pressure in SSBs, , improved understanding of optimizing the CAM microstructure for balanced ion and electronic transport, , lack of problems with O 2 gas evolution as observed in oxide cathodes, ,, progress made on high energy density anodes (Li metal and Si) for SSBs, , and the growing need to diversify cathode chemistries. , …”
Section: Beyond Pure Sulfur: Opportunities With Transition Metal Sulf...mentioning
confidence: 99%
“…14 Moreover, many membrane materials show poor thermal stability during battery operation, which should be considered in the case of specific high-temperature applications. 15,16 Lithium-metal hybrid flow batteries (Li-HFBs) also demand a membrane with a supreme tolerance to the lithium anode, which remains challenging for known solutions. 17 To create an appropriate membrane, one should work not only on the material design but also on improved fabrication and characterization techniques.…”
Section: Introductionmentioning
confidence: 99%